2019
DOI: 10.1038/s41598-019-56295-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced TRPM8 expression underpins reduced migraine risk and attenuated cold pain sensation in humans

Abstract: Multiple genome-wide association studies have identified non-coding single-nucleotide variants (SNVs) near (e.g., rs10166942[C]) or within (rs17862920[T]) the TRPM8 gene that encodes a cold thermosensor is associated with reduced migraine risk. Furthermore, rs10166942[C]) and rs10166942[T]) are more prevalent in populations that reside in hotter and colder climates, respectively. Here we assessed whether these alleles affect TRPM8 expression in humans and human physiologic responses to cold challenge. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…Besides TRPV1 and TRPA1, TRPM8 receptors are expressed in TG neurons (Figure 2). TRPM8 is interesting, because genome-wide association studies showed that it may be implicated in migraine [107,108], i.e., more specifically, single-nucleotide variants near or within the TRPM8 gene resulting in reduced TRPM8 expression are associated with reduced risk for migraine [109]. TRPM8 has been identified as a sensor for environmental cold [57] and low body temperature [110] but experimental work on trigeminal nociceptive functions is contradictory.…”
Section: Signals Sensitizing Trigeminal Nociceptors-involvement and Imentioning
confidence: 99%
See 1 more Smart Citation
“…Besides TRPV1 and TRPA1, TRPM8 receptors are expressed in TG neurons (Figure 2). TRPM8 is interesting, because genome-wide association studies showed that it may be implicated in migraine [107,108], i.e., more specifically, single-nucleotide variants near or within the TRPM8 gene resulting in reduced TRPM8 expression are associated with reduced risk for migraine [109]. TRPM8 has been identified as a sensor for environmental cold [57] and low body temperature [110] but experimental work on trigeminal nociceptive functions is contradictory.…”
Section: Signals Sensitizing Trigeminal Nociceptors-involvement and Imentioning
confidence: 99%
“…In this context it is very interesting that both TRPV1 and TRPM8 receptor channels are differently involved in the regulation of body temperature [109]. While TRPV1 activation causes a decrease, TRPM8 activation causes an increase in body temperature; the basal activity of both receptor channels counteracts excesses of the body temperature, thereby contributing to homeostasis.…”
Section: Signals Sensitizing Trigeminal Nociceptors-involvement and Imentioning
confidence: 99%
“…Migraines (Gavva et al, 2019;Ling et al, 2019), Glioblastoma (Zeng et al, 2019) Regulation of cerebral arterial vasodilation…”
Section: Trpm8mentioning
confidence: 99%
“…TRPM8 has a polymodal gating and is activated by cold and different cooling compounds, such as menthol and icilin (McKemy et al, 2002). Several single nucleotide polymorphisms (SNPs) related to the TRPM8 gene are associated with either the risk (Ling et al, 2019) or protection (Gavva et al, 2019) from migraines. Although the exact mechanisms are unknown, a possible mechanism for TRPM8-mediated risk of migraine headaches might be related to this channel's role in vasoconstriction regulation, which has been related to migraine development (Jacobs and Dussor, 2016).…”
Section: Trpm8mentioning
confidence: 99%
“…Indeed, genetic manipulation of TRPM8 in mice leads to a loss of environmental cold sensation [ 11 , 17 , 18 ] and even the ability to detect warm [ 19 ]. In humans reduced TRPM8 expression leads to attenuated cold and pain sensation [ 20 ]. Conversely, hyperactivity of the channel plays a central role in disease pain states such as cold allodynia after inflammation or nerve injury [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%